Should indications for laterally extended endopelvic resection (LEER) exclude patients with sciatica? - Kanao, Hiroyuki (J Gynecol Oncol, 2020)
OBJECTIVE: Previously, indications for laterally extended endopelvic resection (LEER) have excluded patients with sciatica because R0 resection has not been deemed possible [1]. Because laparoscopy optimizes visualization and thus provides for meticulous dissection, we hypothesized that R0 resection can be achieved by means of laparoscopic LEER in patients with sciatica. This video article aimed to clarify the technical feasibility of laparoscopic LEER performed for laterally recurrent previously irradiated cervical cancer with concomitant sciatica. METHODS: We investigated technical feasibility of laparoscopic LEER performed as a salvage therapy following abdominal radical hysterectomy and concurrent chemoradiotherapy in a patient suffering laterally recurrent cervical carcinoma with concomitant sciatica. The recurrent tumor involved the right external and internal iliac artery and vein, ileocecum, rectosigmoid colon, right ureter, right obturator nerve, and right sciatic nerve, with a resulting fistula between the tumor and the rectosigmoid colon, and severe sciatica. Resection of all these structures was essential for achievement of R0 status, and such resection means concomitant femoral bypass with prosthetic graft interposition and gastrointestinal/urinary tract resection. RESULTS: Laparoscopic LEER with femoral-femoral artery bypass could be conducted without any postoperative complications. Pathological R0 resection could be achieved, and local recurrence could have been controlled. However, the patient died from liver and lung metastasis at 1 year after this resection surgery. CONCLUSION: Laparoscopic LEER for a laterally recurrent previously irradiated cervical cancer with concomitant sciatica was technically feasible, however, further study involving a greater number of patients and longer follow-up period is warranted to determine the stringent indications.